Perbandingan Metode Blackbox Testing dalam Pengujian Tampilan Pendaftaran Rumah Sakit Hewan - Joosten Joosten; Handoko Handoko; Murdiaty Murdiaty; Elly Elly (Universitas Methodist Indonesia, 2024)
Software can be said to be suitable for use when testing has been carried out. The testing stage is an important element in making software or websites. In making software for animal hospitals, there is no validation and verification so testing is needed. This study uses the information display of the patient registration section of the animal hospital and is tested with two Black Box Testing methods, namely Equivalence Class Partitioning (ECP) and Boundary Value Analysis (BVA). The test results with the ECP method are higher than the invalid ones, so it is necessary to change the input value limit. Then for the BVA test, the percentage of valid is higher than invalid. From the results of the two methods, it is shown that the BVA method is better than the ECP method, so it is necessary to improve the data type section when inputting